Kebijakan Publik dan Praksis 'Democratic Governance' di Sektor Pariwisata - Janianton Damanik (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
Tourism is a public sector that should be operated by stakeholders: government, industry and the public itself in the way of a collaborative management. Appropriateness of the public policy ought to be seen from the planning process which involves the local community and takes their interests into account. This article argues that tourism has been developed through a strong control of government and based on the growth paradigm. This has distorted the role of the government which should be a facilitator to be a single player of tourism development. The industry and public itself are alienated from the decision making processes in tourism. The case of tourism shows that democratic governance has not been implemented well and it is a challenge for the future tourism development.